2020
DOI: 10.1097/jpn.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Bundle in the Prevention of Peri-Intraventricular Hemorrhage in Preterm Newborns

Abstract: The purpose of this study was to evaluate the impact of implementing a care bundle for preventing peri-intraventricular hemorrhage (PIVH) in preterm newborns. A longitudinal, quantitative, quasi-experimental study was conducted with preterm newborns from a neonatal unit. The study was divided into 2 stages: the first consisted of a retrospective cohort of newborns (control group) not exposed to the bundle, and the second consisted of 5 practical steps of implementing a care bundle for preventing PIVH in eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…Higher antenatal steroid coverage may be one of the reasons for lower IVH and PVL in triplet or higher-order multiple births. Over the last several years, changes in the neonatal practices, including better ventilation strategies [ 33 , 39 , 40 ] and adherence to various IVH prevention bundles [ 41 , 42 ], are shown to be associated with an improvement in the incidence of IVH and PVL among preterm patients.…”
Section: Discussionmentioning
confidence: 99%
“…Higher antenatal steroid coverage may be one of the reasons for lower IVH and PVL in triplet or higher-order multiple births. Over the last several years, changes in the neonatal practices, including better ventilation strategies [ 33 , 39 , 40 ] and adherence to various IVH prevention bundles [ 41 , 42 ], are shown to be associated with an improvement in the incidence of IVH and PVL among preterm patients.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in about 45% of extremely preterm infants with a birth weight of <750 g and in about 52% of preterm infants born at <28 weeks' gestation ( 4 , 5 ). About 50% of cases of IVH occur within 1 day after birth, and about 90% occur within 3 days of life ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Widely accepted practices related to such management include (1) maintaining a supine midline with a neutral head position [ 58 ]; (2) tilting the incubator to 10° to 30° to avoid the head-down position [ 58 ]; (3) ensuring minimal handling, including suction [ 69 ]; (4) avoiding rapid flushes and blood withdrawal through intravenous or arterial routes [ 97 ]; (5) avoiding routine endotracheal suction [ 69 ]; and (6) initiating additional intervention for pain or stress relief in the form of non-nutritive sucking and oral breast milk or sucrose [ 41 ]. Several studies have indicated that neonatal neuroprotective care bundles that incorporate these practices can reduce the incidence and severity of IVH; however, studies that have applied such practices have obtained inconsistent results [ 23 , 34 , 39 , 85 ]. Therefore, additional studies are required to develop optimal management practices.…”
Section: Postnatal Strategymentioning
confidence: 99%